Approximation of semi-groups in the sense of trotter and asymptotic mathematical modeling in physics of continuous media - Christian Licht (2020)
© 2019 American Institute of Mathematical Sciences. All Rights Reserved. We derive several models in Physics of continuous media using Trotter theory of convergence of semi-groups of operators acting on variable spaces.